Makna Wayang Golek si Cepot pada Masyarakat Sunda Milenial dan Generasi Z - Limelta, Andrew; Paramita, Sinta (Koneksi, 2020)
In 2003 wayang was recognized by UNESCO as a global masterpiece as well as an intangible cultural heritage. Sundanese culture recognizes the legacy of wayang golek originating from the West Java region, and is usually realized through the display of props or puppets as a dualistic depiction of Javanese minds. In puppet show there are characters and characters that are played, but usually people are more familiar with the character of the Cepot who is considered as a entertainer and identity of the Sundanese. The purpose of this study was to see the meaning of the Cepot figure in puppet show art towards millennial Sundanese people and generation Z. The theories used in this study were the theory of communication, puppetry, and the concept of meaning. In this case the data obtained through the results of observations and interviews. The conclusion in this study is that the Sundanese generation of generation millennial and generation Z considers the puppet show as an important art, but no longer as the main consumption. Besides that, there is a loss of elements from the Cepot character in the puppet show, even the Sundanese people consider the Cepot figure only as an entertaining figure. Pada tahun 2003, wayang diakui oleh UNESCO sebagai karya agung dunia sekaligus warisan budaya tak benda. Budaya Sunda mengenal warisan wayang golek yang berasal dari wilayah Jawa Barat, dan biasanya direalisasikan melalui pertunjukan alat peraga atau boneka sebagai penggambaran alam pikiran orang Jawa yang dualistik. Dalam kesenian wayang golek terdapat tokoh dan karakter yang dimainkan, namun biasanya masyarakat lebih mengenal tokoh si Cepot yang dianggap sebagai penghibur dan jati diri orang Sunda. Tujuan penelitian ini adalah untuk melihat makna tokoh si Cepot dalam kesenian wayang golek terhadap masyarakat Sunda milenial dan generasi Z. Teori yang digunakan dalam penelitian ini adalah teori komunikasi, wayang, dan konsep makna. Dalam hal ini data yang diperoleh melalui hasil dari observasi dan wawancara. Kesimpulan dalam penelitian ini adalah bahwa masyarakat Sunda generasi milenial dan generasi Z menganggap kesenian wayang golek sebagai suatu kesenian yang penting, namun bukan lagi sebagai konsumsi utama. Selain itu adanyaunsur dari tokoh si Cepot yang hilang dalam wayang golek. Bahkan masyarakat Sunda menganggap tokoh si Cepot hanya sebagai tokoh penghibur.